Ferromagnetism and optical properties of SnS2 doped with two impurities: first-principles calculations. Issue 11 (11th March 2021) - Lin, Long; Chen, Yujin; Tao, Hualong; Yao, Linwei; Huang, Jingtao; Zhu, Linghao; Lou, Mengsi; Chen, Ruixin; Yan, Longbin; Zhang, Zhanying
Abstract : The contribution of Fe and Cr to the magnetic properties in (0, 1) doped SnS2 configurations can be seen intuitively. Abstract : Based on the first principles of the GGA method, the magnetic and optical properties of intrinsic SnS2 ; Fe, Cr mono-doped SnS2 ; and (Fe, Cr) co-doped SnS2 are studied. The results show that the ground states of Fe, Cr mono-doped SnS2 are spin polarized, and the magnetic moments caused are 1.99 μ B and 3.00 μ B, respectively. The magnetic moment of Fe mono-doped SnS2 is mainly produced by Fe:3d orbitals, and the magnetic moment of Cr mono-doped SnS2 is mainly produced by Cr:3d and Sn:4d orbitals. We calculate that in the (Fe, Cr) co-doped SnS2 system, Fe, Cr and the adjacent S atoms form a strong hybrid, that is, the closest S atom between Fe and Cr atoms mediates the spin polarization and ferromagnetic (FM) coupling. This promotes the formation of a Fe:3d–S:3p–Cr:3d coupling chain, so that (Fe, Cr) co-doped SnS2 obtains FM stability. In addition, with the introduction of Fe and Cr atoms, the absorption coefficient is the largest in the long-wavelength infrared region of 0.23–1.63 eV. This shows that Fe and Cr doping can make up for the lack of absorption of intrinsic materials in the infrared region. In summary, Fe, Cr doped SnS2 dilute magnetic semiconductors may be a good candidate in the field of spintronic devices.